Identification, Characterization and Functional Analysis of C-Class Genes Associated with Double Flower Trait in Carnation (Dianthus caryphyllus L.) - Wang, Qijian (Plants (Basel), 2020)
Flowers with more petals are of more ornamental value. It is well known that AGAMOUS (AG) is the core member of the C-class gene which plays an essential role in double flower formation and identification of stamens and carpels in Arabidopsis thaliana. We searched C-class genes in the genome of the carnation, and found two AG orthologs (DcaAGa, DcaAGb). Phylogenetic analysis showed that the two genes were closely related to the euAG subclade. Then we searched the genomes of other Caryophyllales plants (Beta vulgaris, Spinacia oleracea, Chenopodium quinoa) for C-class genes, and found that their C-class genes all belonged to the euAG subclade. Semi-quantitative PCR (sq-PCR) analysis indicated that the expression of DcaAG genes in the single flower phenotype was higher than that in the double flower phenotype. Quantitative real-time RT-PCR (qRT-PCR) analysis showed that the expressions of DcaAG genes in the flower bud were significantly different from those in the root, stem, and leaf between the single and double flower phenotype carnations, and that DcaAG genes were specifically expressed in the stamen and carpel of carnation. Moreover, the expression of other floral organ identity genes (AP1 and AP2, PI and AP3, SEP1 and SEP3 corresponding to the A-, B-, and E-class of genes, respectively) showed no significant difference in all floral organs between the single and double flower phenotype carnations, suggesting that C-class (DcaAG) genes might play an important role in the double flower phenotype in carnation. Petal loss or decrease, precocious flowering, silique shortening, and seed sterility were observed in 35S::DcaAGa and 35S::DcaAGb transgenic Arabidopsis plants. All these results show that DcaAG genes might affect the petal number negatively and have a specific function in stamen and carpel development in carnation.